Management and long-term outcomes of post stenting coronary pseudoaneurysm: A single-center retrospective analysis - Rujuta Parikh; Riyaz Charaniya; Gaurav Singh; Gourav Behra; Utsav Patel; Krutika Patel; Ashish Garg; Mohit Khare (Heart India)
Background: Coronary artery pseudoaneurysm following implantation of a drug eluting stent (DES) is a lesser known complication. The clinical presentation, natural history and line of management is not well defined in these cases. To define clinical presentation and treatment modalities of patients presenting with coronary pseudoaneurysm post stenting. Materials and Methods: We analyzed 23 consecutive patients presenting to us with coronary pseudoaneurysm post DES implantation between 2015 and 2022 and followed them up till the most recent outpatient department visit. We analyzed demographic data, procedural and stent size used during index percutaneous transluminal coronary angioplasty, hemodynamic and clinical presentation and management strategy and followed them to note any major adverse cardiovascular event with computerized tomographic coronary surveillance. Results: Out of 23 patients enrolled in our study, the clinical presentation varied from as benign as being asymptomatic to as catastrophic as cardiogenic shock. The time of presentation from index coronary stenting to pseudoaneurysm formation varied from 3 days to 8 years. Management depends on hemodynamic stability, underlying pathophysiology, and expected long-term outcome. Conclusion: Coronary artery pseudo-aneurysm following percutaneous stenting is rare and pose a challenge to the treating team. Different pathophysiologies have been described, and depending on them, they may have varied presentation. The treatment plan should be optimized considering the size and progression of aneurysm, the clinical presentation of the patient, concomitant comorbidities like coronary artery disease to be addressed, and anatomy of the affected vessel.